DISSENTING OPINION OF JUDGES IN THE PERSPECTIVE OF SIYASAH SYAR’IYYAH: A Study of the Constitutional Court Decisions No. 1/PHPU.PRES-XXI/2024 and No. 2/PHPU.PRES-XII/2024 (the Presidential Election Results) - Mawarni, Wilda; Wardiono, Kelik (Universitas Islam Negeri Mataram, 2024)
This study delves into the significance and impact of dissenting opinions in Indonesia’s constitutional legal framework, specifically through an analysis of Constitutional Court Decisions No. 1/PHPU.PRES-XXI/2024 and No. 2/PHPU.PRES-XII/2024. In Indonesia, dissenting opinions, though non-binding, play an essential role in the judicial process by offering alternative interpretations and critiques of the majority's rulings. These opinions allow judges to express disagreements rooted in different legal reasoning, often contributing to a richer and more nuanced understanding of the law. By applying the perspective of Siyasah Syar’iyyah—an Islamic governance concept emphasizing justice (’adl) and public welfare (maslahah)—this study frames dissenting opinions as a vital tool for promoting justice and ethical governance within the legal system. The principles of justice and consultation (syura) in Siyasah Syar’iyyah align with the objectives of dissenting opinions, encouraging decision-making processes that are transparent, inclusive, and aligned with the broader interests of society. This research finds that dissenting opinions in the Constitutional Court not only provide critical viewpoints that can refine legal interpretations but also contribute to the legitimacy and resilience of legal policies. Furthermore, dissenting opinions often serve as a corrective mechanism, inspiring future reforms and guiding policymakers toward decisions that uphold equity and societal welfare. This alignment with Siyasah Syar’iyyah underscores the importance of dissenting opinions in fostering a legal environment that remains responsive to evolving social dynamics and rooted in the pursuit of substantive justice. Ultimately, this study highlights how dissenting opinions can act as a bridge between contemporary legal practice and foundational Islamic principles, ensuring that the ideals of Siyasah Syar’iyyah are meaningfully integrated into Indonesia’s legal landscape.